Research Progress and Technological Application Prospects of Comprehensive Evaluation Methods for Egg Freshness - Zhouyang Gao; Jiangxia Zheng; Guiyun Xu (Foods)
Eggs, recognized as a “complete nutritional food”, constitute a crucial source of high-quality protein and maintain an essential position in China’s animal protein supply system. However, extended storage periods induce biochemical degradation, including protein denaturation, air cell expansion, and microbial growth, substantially affecting both food safety and nutritional value. As consumer demand for food quality assurance increases, research in egg freshness evaluation has made substantial progress. While existing studies have focused on isolated detection methods for egg freshness, there remains a critical gap in systematically integrating multidisciplinary approaches and evaluating their synergistic potential for comprehensive quality assessment. This review systematically categorizes conventional and emerging detection methodologies, including sensory assessment, physical characterization, chemical analysis, and intelligent detection technologies. The paper presents a comprehensive analysis of current research developments while offering perspectives on practical applications and future directions for egg freshness evaluation systems.